Studi Jajak Pendapat Kebijakan Pendidikan Menengah Universal*) - Subijanto – (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2014)
The aims of polling study for universal secondary education is to gather responses from the society concerning on the implementation of universal secondary education policy by the Ministry of Education and Culture (MoEC). The method used in this study is polling and data collection using questionare. Respondents are chosen by using the purposive sampling technique. The result of the study shows that generally most of the stakeholders fully support the universal secondary education policy. This policy is viewed to be able: a) to overcome problems of inaccessible education by each secondary school age children due to economic, gheographic, and technology problems; b) to improve the vocationa secondary education graduate readinessm to work and to improve the national, regional, and local gross participation rate (APK); c) to improve the nation competitiveness, quality, and students capacity; d) to improve the compositionof general secondary school and vocational school in relation with the local needs; e) to increase fully needed financial support from central government, provincial government, and district/municipality government, societies including enterpreneurships and industries; and f) to improve the quality of teachers and administrators, educational facilities which are fully needed. Thus, the teaching model which are relevant to the studenâ€™s needs and match the needs of industries and enterprices would be met.Â ABSTRAKStudi jajak pendapat (polling) tentang kebijakan pendidikan menengah universal (PMU) bertujuan untuk memperoleh tanggapan masyarakat terkait dengan Kementerian Pendidikan dan Kebudayaan mengimplementasikan program PMU. Studi dilakukan melalui jajak pendapat (polling) dengan membagikan kuesioner kepada responden. Pemilihan responden ditentukan dengan teknik purposive sampling. Hasil jajak pendapat menunjukkan bahwa secara umum sebagian besar masyarakat setuju terhadap kebijakan penyelenggaraan PMU dan bersedia membantu penyelenggaraan sosialisasi kebijakan PMU. Kebijakan ini dinilai dapat: a) menanggulangi kesulitan akses bagi setiap anak usia sekolah menengah karena faktor ekonomi, geografi, dan teknologi; b) meningkatkan kesiapan kerja bagi lulusan sekolah menengah kejuruan (SMK) dan dapat meningkatkan target angka partisipasi kasar (APK) di tingkat nasional/ provinsi/ kabupaten/kota secara bertahap; c) meningkatkan daya saing bangsa, mutu, dan daya tampung peserta didik; d) meningkatkan proporsi jumlah SMA:SMK sesuai potensi dan kebutuhan daerah; e) meningkatkan dukungan anggaran baik Pemerintah Pusat, pemerintah daerah dan masyarakat termasuk DUDI; f) meningkatkan tenaga pendidik dan tenaga kependidikan serta fasilitas sarana prasarana sangat diperlukan, sehingga dukungan terhadap model pembelajara yang relevan dengan kebutuhan siswa dan kebutuhan lapangan kerja dapat terpenuhi.